2014
DOI: 10.1583/13-4548r.1
|View full text |Cite
|
Sign up to set email alerts
|

Nitinol Stent Implantation in the Superficial Femoral Artery and Proximal Popliteal Artery: Twelve-Month Results From the Complete SE Multicenter Trial

Abstract: In this multicenter trial, primary implantation of a new-generation self-expanding nitinol stent in the SFA and PPA was associated with a low rate of TLR and sustained clinical benefit at 12 months without stent fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 28 publications
2
40
0
2
Order By: Relevance
“…TLR‐free rates for SuperNOVA are similar to those of other bare‐metal stent studies for SFA, especially when lesion length is considered. The Kaplan–Meier estimate for the 12‐month TLR‐free rate for the core matrix in SuperNOVA (89.7%) is within the range of 87–91% defined by other studies with similar stent lengths ; the TLR‐free rate for the entire matrix (86.5%) is likewise similar to the rate reported for another study with an expanded stent length matrix (86.1%) . The 24‐month TLR‐free rates observed for the core and full stent length matrices in SuperNOVA are also similar to reported rates from studies with similar stent lengths .…”
Section: Discussionsupporting
confidence: 82%
“…TLR‐free rates for SuperNOVA are similar to those of other bare‐metal stent studies for SFA, especially when lesion length is considered. The Kaplan–Meier estimate for the 12‐month TLR‐free rate for the core matrix in SuperNOVA (89.7%) is within the range of 87–91% defined by other studies with similar stent lengths ; the TLR‐free rate for the entire matrix (86.5%) is likewise similar to the rate reported for another study with an expanded stent length matrix (86.1%) . The 24‐month TLR‐free rates observed for the core and full stent length matrices in SuperNOVA are also similar to reported rates from studies with similar stent lengths .…”
Section: Discussionsupporting
confidence: 82%
“…Recently, the Complete Self-Expanding trial that used a new nitinol selfexpanding stent to treat femoropopliteal disease demonstrated a low rate of target lesion revascularization (TLR) and no stent fractures at 12 months. 45 The Supera Interwoven Nitinol Stent Outcomes in Above-Knee Interventions (SAKE) study also showed high rates of patency at 6 and 12 months with no stent fractures for femoropopliteal disease treated with the novel interwoven-wire Supera stent. 46 Furthermore, the outcomes after popliteal stenting with the Supera stent from the Leipzing Supera popliteal artery registry showed 6-and 12-month primary patency rates of 94.6% and 87.7%, respectively, with a significant increase in mean ABI (0.58 versus 0.97; P<0.001) and no radiographic evidence of stent fracture at 15 months.…”
Section: Femoropopliteal Diseasementioning
confidence: 99%
“…Bare metal stents (BMS) have demonstrated improved short-term outcomes compared to PTA, [5][6][7][8][9] with longer term patency rates of 60-75%. [10][11][12] However, in-stent restenosis (ISR) and stent fractures remain concerns.…”
mentioning
confidence: 99%